Observations on the Heparin Neutralizing Activity of Outdated Platelet Concentrates - Griffiths, B L; Collins, J R; Huntsman, R G (Thrombosis and Haemostasis, 1984)
A crude extract of outdated, washed, frozen and thawed, platelet concentrates was prepared and optimally diluted for use in the A. P. T. T. test as a source of platelet phospholipid (P. F. 3). The extract contained, in addition to P.F. 3, active heparin neutralizing activity (P. F. 4), which was able to neutralize plasma heparin up to a concentration of approximately 0.8 units/ml plasma. Although these observations are of a preliminary nature, it is felt that the extract can be used to follow the “intrinsic” coagulability of plasma samples from patients receiving therapeutic heparin. Utilizing the A. P. T. T. test system, the determination of coagulability and the neturalization of heparin result from the use of this extract in a single test.
Keywords: Platelet factor 4; Heparin neutralizing activity; Activated partial thromboplastin time (A.P.T.T.)